Divalent NI Compounds: Identifying new Carbocyclic Carbenes to Design Nitreones using Quantum Chemical Methods. Issue 31 (10th September 2020) - Patel, Neha; Arfeen, Minhajul; Singh, Tejender; Bhagat, Shweta; Sakhare, Ajay; Bharatam, Prasad V.
Abstract: Nitreones are compounds with oxidation state 1 at the nitrogen, these compounds carry formal positive charge as well as two lone pairs of electrons at nitrogen center. These compounds are also known as divalent N I compounds and can be represented with the general formula L → N + ← L, where L is an electron donating ligand. In the recent past, several divalent N I compounds have been reported with L = N ‐heterocyclic carbene (NHC), remote N ‐heterocyclic carbene ( r NHC), carbocyclic carbene (CCC) and diaminocarbene. Recently, our group reported that a novel six‐membered CCC (cyclohexa‐2, 5‐diene‐4‐[diaminomethynyl]‐1‐ylidene) can stabilize N + center in nitreones. As an independent carbene, this species is very unstable. In this work, modulation of this CCC using (a) annulation, (b) heterocyclic ring modification, (c) substitutions adjacent to the carbenic carbon, (d) exocyclic double bond insertion and (e) ring contraction, has been reported. These modulations and quantum chemical analyses helped in the identification of five new six‐membered CCCs which carry improved donation and stability properties. Further, these CCCs were employed in the design of new divalent N I compounds (nitreones) which carry coordination bonds between ligands and N + center. The molecular and electronic structure properties, and the donor→acceptor coordination interactions present in the resultant low oxidation state divalent N I compounds have been explored. Abstract : Divalent N I compounds are novel species with N + as electron acceptor. These species are reported mostly with NHCs and r NHCs as electron donor. CCCs are newly emerging carbenes having interesting σ‐donating properties. Here, we present a novel six‐membered CCC (cyclohexa‐2, 5‐diene‐4‐[diaminomethynyl]‐1‐ylidene) and its structural modifications to improve donating properties. Five new CCCs carrying improved donation and stability properties were selected to design a new class of nitreones. The results of various quantum chemical studies suggest low oxidation state at N + center.